Study Of Care Comparation Of Kangaroo Method Treatment And Massage Therapy Methods On Weight Improvement In 0-28 Day Of Lbw In Room Perinatology - Anita Theodora Fitriani Mallisa (Journal of Applied Nursing and Health, 2019)
Infants Low Birth Weight (LBW) is a newborn baby who weighs 2500 grams or lower regardless of gestation. Kangaroo method treatment and baby massage therapy can be given for therapy to increase the baby's weight in LBW. Objective To find out the differences in Kangaroo Method Treatment and Infant Massage Therapy on Increasing Body Weight in LBW Age 0-28 Days in the Perinatology Room of Torabelo Regional Hospital, Kab. Sigi Central Sulawesi. The design used in the study was Quasi Population Experiments which were all low birth weight babies. The sample size was 16 respondents using the Independent Variable Purposive sampling technique. The research was kangaroo method treatment and baby massage. The dependent variable is the baby's weight. Data was collected using a questionnaire, then the data were analyzed using the Independent t test with a significance level of α ≤ 0.05. The results of the PMK influence test using paired t test obtained p = 0,000 with a <0,05 so that Ho was rejected, and H1 was accepted which means there was an effect of Kangaroo Method Treatment on Increased Body Weight on LBW, there was the effect of baby massage treatment on increasing body weight on LBW. The results of different tests of PMK intervention with infant massage using Independent t test obtained p = 0,000 with a <0,05 so that Ho was rejected, and H1 was accepted which meant there was a difference in Kangaroo Method Care and Infant Massage Therapy Against Increased Body Weight at LBW Age 0- 28. There are differences in Kangaroo Method Treatment and Infant Massage Therapy Against Increased Body Weight at LBW Age 0-28 Days in the Perinatology Room of Torabelo Regional Hospital, Kab. Sigi Central Sulawesi.